2021
DOI: 10.1186/s44147-021-00023-x
|View full text |Cite
|
Sign up to set email alerts
|

Travelers’ attitude towards carpooling in Islamabad

Abstract: Islamabad, being the capital of Pakistan, is attracting every business. Thus, the city is growing towards traffic congestion as the city’s car ownership rate is rapidly growing. In such a situation, for successful implementation, the policymakers need to understand the public acceptance of carpooling services based on its key motives and constraints. This research explores the key motives and constraints to the introduction scenarios of carpooling service in Islamabad. A stated preference questionnaire survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Cronbach's Alpha, often called CRA, was utilized to determine whether the questionnaire was consistent and reliable. The values of the CRA can range anywhere from 0 to 1, with values closer to 1 indicating more reliability [46,47]. According to the findings of this investigation, the computed CRA value was recorded as 0.74, indicating that the internal consistency of the questionnaire can be regarded as satisfactory [67].…”
Section: Descriptive Analysismentioning
confidence: 61%
See 2 more Smart Citations
“…Cronbach's Alpha, often called CRA, was utilized to determine whether the questionnaire was consistent and reliable. The values of the CRA can range anywhere from 0 to 1, with values closer to 1 indicating more reliability [46,47]. According to the findings of this investigation, the computed CRA value was recorded as 0.74, indicating that the internal consistency of the questionnaire can be regarded as satisfactory [67].…”
Section: Descriptive Analysismentioning
confidence: 61%
“…This form of transportation reduces emissions that keep society safe and natural while being highly environmentally friendly. As identified in the existing research, various models [46,47] have been developed to study the influence of travelers' perceptions on adopting carpooling as a mode of transportation. However, in this research, the mediating effect of mode choice has also been incorporated to study its impact on the relationship between traveler perception and the tendency to carpool.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Ride-pooling attitude refers to residents ' positive or negative emotions about possible scenarios in ride-pooling [23]. Zhang Xin et al evaluated the factors affecting the intention of ride-pooling by analyzing the questionnaire data of 597 private car owners in Tianjin, China, and found that the attitude of ride-pooling has a mediating effect in the model [24].…”
Section: The Mediating Role Of Ride-pooling Attitudementioning
confidence: 99%
“…The corresponding test results are shown in Table 6. The chi-square/degrees of freedom (χ 2 /d f ), root mean square error of approximation (RMSEA), comparative fit index (CFI), Tucker-Lewis Index (TLI), and standardized root mean square residual (SRMR) indicators are within acceptable limits [62,75], indicating that the overall fitness of this structural equation model is good.…”
Section: Analysis Of Reliability and Validitymentioning
confidence: 99%